Do financial market variables show (symmetric) indicator properties relative to exchange rate returns? - Olli Castrén (European Central Bank (ECB), 2004)
This paper assesses the contemporaneous, leading and lagging indicator properties of financial market variables relative to movements in six major developed country currency pairs. As indicator variables changes in various relative asset prices, short-term portfolio flows and currency options data are used. We find that changes in equity index differentials, short-term speculative flows and risk reversals on currency options prices exhibit consistent contemporaneous indicator properties and leading indicator properties for several currency pairs. Since 1999, changes in short-term interest rate differentials have gained importance as indicators. The best indicator variables explain over 50% of monthly returns of the USD/EUR and GBP/USD exchange rates and over 60% of the appreciation and depreciation episodes of the USD/EUR and JPY/EUR currency pairs.
Keywords: F31; F32; G15; 330; asset prices; Capital flows; Exchange Rates; GMM; leading and lagging indicators; logit estimation; market microstructure